TREND IN CHILD VIOLENCE IN INDONESIA AND GOVERNANCE - Zalsabil Ayusazky; Dian Suluh Kusuma Dewi (DIA: Jurnal Administrasi Publik, 2023)
This article aims to know the trend of violence against children in Indonesia and the steps the Indonesian government to get over it with the use of approach analysis of public policy and collaborative governance. Study this uses a qualitative approach. Data is collected from Dimensions, consisting of 437 articles from journals, national and international, books support, and newsletters. Collected data was then processed using the applications VosViewer and Nvivo 20, both used to reveal moderate issues and trends about a violent children. Analysis results disclose that the government has made policy through the Undang-Undang Nomor 35 Tahun 2014 concerning the protection of children and the Peraturan Menteri Agama Nomor 73 Tahun 2022 concerning handling through socialization, learning, strengthening governance, strengthening culture and activities, other following need. And prevention in the form of reporting, protection, assistance, prosecution, and recovery of victims. Whereas the protection of the children applied with facilities for children and productive activities to fulfill children's education rights. The government also supervises assurance fulfillment suitable base and finishes related issues with victims of violence physique as well as mental and violation rule applicable law. The form of collaborative governance has also been done government about City/ District Decent Son throughout regions in Indonesia and the National Commission of the Children and Women Protection in overcoming problem hardness and fulfillment right children in Indonesia.